(Inter)cultural components in EFL teaching: evidence from pre-service teachers’ projects - Monika Kusiak (Educational Role of Language Journal, 2020)
Intercultural Communicative Competence (ICC) is an object of recent studies in the areas of applied linguistics, education and teacher training, those discussing theoretical underpinnings of the intercultural approach and those focusing on classroom implications. In Poland, fostering FL learners’ ICC has become an ambitious goal of both FL education and FL teacher training. The paper discusses the results of the study which examined the empirical projects produced by pre-service FL teachers, participants of EFL training organized within a university setting. The topics of all the projects revolve around introducing intercultural elements in EFL teaching. The analysis examined the aims of the students’ projects, the methodology applied and the theoretical perspectives that underlined the studies. The findings allowed the author of the paper to construct the profile of a FL teacher who would be prepared to promote the principles of the intercultural approach in FL teaching. The paper may be of interest to those involved in FL education, including FL teacher training.